Multidisciplinary Synergy of Health Workers as an Effort to Improve Public Health Status - Ema Pristi Yunita (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
The low level of public knowledge of the importance of preventing diseases and maintaining health can increase morbidity and mortality. In this community service, counseling and integrated health services were provided by seven health study programs at Universitas Brawijaya (UB). This community service aimed to improve public health status and identify the correlation between education level and public behavior and their health condition. All health workers wrote the health status of the participants on the community health cards. The participants were asked to answer questionnaires as a feedback process and an analysis of the activity. A total of 95.33% of the participants stated that these activities were useful while 4.67% stated that the activities were useless. The results of the gamma correlation test showed a significant correlation between education level and public behavior towards complaints about aches and pains, coughs and colds, diarrhea, chest pains, and itching. On complaints about aches and pains and abdominal pain, the higher the education level, the worse the behavior in dealing with the complaints. Collaborative activities among health workers are needed to overcome public health problems. A high education level of the public does not always guarantee the accuracy of certain actions chosen to overcome various early symptoms of diseases. Therefore, the role of health workers is needed in providing health education to the public regardless of their education levels.